AB0254 Gastrointestinal health of ra patients - from top to tail. (23rd January 2014) - Waller, R.; Williamson, L.; Collins, D.; Price, E.
Abstract : Background: Gastrointestinal problems are common but not well studied in RA patients. Symptoms may affect patient health, quality of life and concordance with medication. Objectives: To assess the prevalence, severity and nature of gastrointestinal (GI) symptoms in our RA patients. Methods: A 10 point questionnaire was posted to all patients with a diagnosis of RA on our electronic database. Patients were invited to attend clinic, where a more detailed GI history and examination, including medication and dental history was undertaken. Results: Of 597 questionnaires sent, 301 (50%) were returned. 129 patients were assessed in clinic: 67% were female; median age 62 (range 31-91); median disease duration 13 years (range 1 – 49); mean DAS score 3.04 (range 1.1 – 6.19). Gastrointestinal symptoms : 226 (75%) of patients reported some form of GI problems in the self reported questionnaire. 51 (17%) reported daily GI symptoms; 33 (11%) reported 3 or more GI symptoms on a weekly basis. Of weekly symptoms, the most common were indigestion (25%), bloating (24%), abdominal pain (18%), diarrhoea (18%). Dental disease was common in clinic patients: 109 (84%) had fillings; 11 (<1%) patients had normal dentition; 28 (22%) had poor gum health, including loose teeth or gingivitis; 70 (54%) patients had a dry or coated tongue; 42 (32%) of patients reported mouth ulcers 36 patients (28%) had haemorrhoids. Medication: There was a high rate of medication use with potential GI side effects (GI toxic meds) in clinic patients: bisphosphonates 34 (26%); prednisolone 12 (9%); NSAIDS 64 (50%). 15 patients (12%) were on at least 2 of the above. 52 patients (40%) were on a PPI. 31/52 were taking 1 of the above medications. 41% of patients on GI toxic meds were taking a PPI compared to 39% of those not. Patients taking potentially GI toxic meds were more likely to suffer GI symptoms on at least weekly basis. (see table ) Co-prescription of a PPI did not reduce this rate, whereas a PPI appeared to be protective in those not taking GI toxic meds. Conclusions: GI symptoms were common in our RA population, even in those patients not taking potentially GI toxic meds. GI problems could commonly affect any part of GI tract, from mouth to anus. Rheumatologists should not forget to enquire about GI symptoms during routine clinical review. Disclosure of Interest: None Declared